P774 Comparison of disease burden of ulcerative colitis patients treated with biologics/biosimilars in remission and not in remission across the EU5. (16th January 2018) - Lu, Y; Baskett, A; Triggs, H; Haven, B; Collins, P
Abstract: Background: Disease remission is a key target while managing patients with ulcerative colitis (UC). Methods: A multi-center medical chart-review study of UC patients was conducted among physicians (majority: gastroenterologists) in hospitals/private practices to collect de-identified data on patients who are currently on a biologic/biosimilar or recently discontinued one within past three months. Physicians from the five EU countries (5EU) were screened for practice-duration and patient-volume and recruited from a large panel to be geographically representative in each country. Patient charts of 4 successive patients visiting each center/practice during study period were selected. Physicians abstracted patient diagnosis, treatment patterns/dynamics and patient symptomatology/disease status (incl. assessment of "disease remission", per physician clinical judgment). Results: In 3Q2017, 213 physicians abstracted 792 eligible current biologic/biosimilar UC patient charts; patient mean age: 41 years, female: 42% (range: 37% (UK)–45% (Germany/Spain)). Geographic distribution of patients were—UK/France: 21% each, Germany/Italy: 20% each, Spain: 19%. Percentage patients currently on first-line biologic: 82% (range: 73% (France)–89% (Germany)), on second-line biologic: 16% (range: 9% (Germany)–24% (France), on ≥third-line biologic: 2% (range: 1% (Spain)–3% (France)). Overall, 72% of current biologic/biosimilar patients were in remission. Remission rate differed by biologic lines: first-line: 73%, second line: 68%, ≥third line: 64%. Average length of remission: 12 months varied by country (range 8 months (UK)–15 months (France/Spain)). Patient current disease-severity (mild:moderate:severe) differed significantly between those in remission vs. those who were not: EU5, 68%:30%:2% vs. 12%:54%:35%. Percent usage of tests between those in remission vs. those who were not differed: Calprotein 65% vs. 57%, ESR 53% vs. 50%, CRP 97% vs. 85%, and Mayo 58% vs. 56%. Among those with lab measures, results differed between those in remission vs. those who were not: mean Calprotein: 116.5 vs. 473.6, mean ESR (mm/h): 16.3 vs. 53.7, CRP (mg/l): 7.3 vs. 33.9 and Mayo 2.6 vs. 6.4. Conclusions: The cohort of UC biologic/biosimilar patients who were deemed to not be in remission were less likely to be tested for Calprotein, ESR, CRP and Mayo than those in remission. Results indicate a greater disease burden for the patients not in remission. As the line of treatment increased, proportion of individuals achieving remission decreased. These observed patterns warrant further scrutiny to determine the best practices and improve remission rates, thereby alleviating patient burden.